"Going down the Rabbit Hole": Relational Tensions Experienced by Alienated Parents during Reconnection. Issue 5 (4th July 2022) - Mullis, Michaela D.; Fisher, Carla L.; Wolf, Bianca
ABSTRACT: Parental alienation (PA), typically identified in divorced families, is a form of nonvoluntary family distancing wherein one parent employs maladaptive communication patterns to sever the relationship between the other parent and child(ren). This study examines the reconnection phase of PA from the alienated parent perspective, elucidating tensions salient to PA as well as enacted communication management strategies. Alienated parents who experienced PA and reinitiated contact were recruited to participate in retrospective interviews. Four dialectical tensions and corresponding communication strategies were identified. Data provide a more holistic understanding of PA reconnection experiences. Findings are vital to building supportive resources for PA.